Foreign Language Effect on Dishonesty - Yang, Xiaolan; Li, Li; Li, Rui (Frontiers in Psychology, 2021)
The purpose of this paper is to investigate whether the use of foreign languages affects individuals’ dishonesty. We recruited native Chinese speakers who can speak English as a foreign language at universities in China, and they were randomly assigned to a native language (NL) or foreign language (FL) condition. Participants in each condition were required to finish the same tasks, in which they would benefit more from lying; the tasks were administered in either Chinese or English. We conducted one die-roll game in Study 1 and one cheap-talk sender-receiver game in Study 2. In both Study 1 and Study 2, we found that the proportion of lying was significantly lower in the FL condition than in the NL condition. Our results imply that the FL effect on dishonesty may be due to the cognitive load of communicating in a FL.